2018
DOI: 10.1111/bjso.12288
|View full text |Cite
|
Sign up to set email alerts
|

The experience of deprivation: Does relative more than absolute status predict hostility?

Abstract: The present research examined the causal effects of absolute and relative status on experienced deprivation and hostility. On the basis of the theory of relative deprivation, we reasoned that the subjective experience of being worse off than others is a better predictor for hostility than is the absolute level of how well‐off people are. Indeed, three experiments showed that relative more than absolute status has an impact on aggressive affect. That is, even when objective resources were high, people were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…The participants in the study deemed the use of derogatory name-calling and attributing any wrongdoing to the foreign nurse educators as hostile behaviour. This finding is strongly supported by Greitemeyer and Sagioglou ( 2018 ); the study found that it is common for people of similar social networks to become hostile to those different from their own. Such hostility may result in both social and economic exclusion, as is the case with the current study.…”
Section: Discussionsupporting
confidence: 66%
“…The participants in the study deemed the use of derogatory name-calling and attributing any wrongdoing to the foreign nurse educators as hostile behaviour. This finding is strongly supported by Greitemeyer and Sagioglou ( 2018 ); the study found that it is common for people of similar social networks to become hostile to those different from their own. Such hostility may result in both social and economic exclusion, as is the case with the current study.…”
Section: Discussionsupporting
confidence: 66%
“…According to relative deprivation theory (Crosby, 1976; Pettigrew, 2016; Runciman, 1966), a precondition for feeling deprived, or angry and resentful about having lesser resources, is believing that one deserves to have more. It is well‐documented that absolute deprivation , or having few resources alone, does not predict strong feelings of angry resentment (Greitemeyer & Sagioglou, 2019; Liu, et al., 2019; Smith, et al., 2012). Instead, feelings of resentment depend, among other things, on feeling that you deserve better.…”
Section: Stress and Changementioning
confidence: 99%
“…On the other hand, the confrontation with a silver-lining and positive outlook could potentially lead to a break with these common interests as self-interest is now the main priority. Research has shown that a positive economic outlook does not necessarily imply satisfaction (Dambrun et al, 2006; Greitemeyer and Sagioglou, 2019; Ishida et al, 2014; Power, 2018). Referring to China, Brockmann et al (2009) found that despite massive increases in income, happiness decreased considerably.…”
Section: Theory and Hypotheses: How Information About The Economic Consequences Of Crises Impacts Feelings Of Disadvantagementioning
confidence: 99%
“…Thus, obvious improvements could inadvertently induce relative deprivation (Smith and Huo, 2014: 235). Comparisons with others in particular might prompt relative deprivation when people ask why others are even better off (Greitemeyer and Sagioglou, 2019; Smith and Huo, 2014). Relative deprivation is prompted by the relative standing of the individuals when compared to others and not by his/her absolute position.…”
Section: Theory and Hypotheses: How Information About The Economic Consequences Of Crises Impacts Feelings Of Disadvantagementioning
confidence: 99%
See 1 more Smart Citation